2023
DOI: 10.3389/fbioe.2023.1127908
|View full text |Cite
|
Sign up to set email alerts
|

MiR-20a promotes osteogenic differentiation in bone marrow-derived mesenchymal stem/stromal cells and bone repair of the maxillary sinus defect model in rabbits

Abstract: Introduction: This study aimed to determine whether miR-20 promoted osteogenic differentiation in bone marrow-derived mesenchymal stem/stromal cells (BMSCs) and accelerated bone formation in the maxillary sinus bone defect model in rabbits.Methods: BMSCs were transfected with miR-20a or anti-miR-20a for 12 h, followed by detection of RUNX2, Sp7 mRNA, bone morphogenetic protein 2 (BMP2), and RUNX2 protein expression. Alkaline phosphatase (ALP) activity and Alizarin Red S staining were used to detect calcified n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a fibrous collagen, COL-1 is the most abundant and vital protein in the human body and is particularly important for developing bone tissue ( Chen et al, 2021 ). BMP-2 can induce the directional differentiation and proliferation of undifferentiated mesenchymal stem cells into chondrocytes and osteoblasts and promote the differentiation and maturation of osteoblasts ( Wang et al, 2023 ). This suggests that the osteogenic properties of the scaffold were enhanced after the addition of β-TCP.…”
Section: Resultsmentioning
confidence: 99%
“…As a fibrous collagen, COL-1 is the most abundant and vital protein in the human body and is particularly important for developing bone tissue ( Chen et al, 2021 ). BMP-2 can induce the directional differentiation and proliferation of undifferentiated mesenchymal stem cells into chondrocytes and osteoblasts and promote the differentiation and maturation of osteoblasts ( Wang et al, 2023 ). This suggests that the osteogenic properties of the scaffold were enhanced after the addition of β-TCP.…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, a decrease in the expression of miR-34a, miR-96-5p, miR-199a, and miR-20a was observed, while miR-486b-5p showed higher expression in extracellular vesicles released by osteoclasts (Figure 2) [116]. In all cases, these miRNAs have been associated with the ability to promote osteoblast differentiation, with miR-96 acting through the Wnt pathway and miR-20a acting through the bone morphogenetic protein (BMP)/runt-related transcription factor 2 (RUNX2) pathway [117][118][119][120][121][122]. Another miRNA capable of promoting osteoblast differentiation is miR-324 (Figure 2).…”
Section: Exosomal Mirnas With the Ability To Promote Osteoblast Diffe...mentioning
confidence: 98%